A Review of the Literature on Factors That May Influence Entrepreneurial Intention among University Students - Lamyaa Massouati; Noureddine Abdelbaki (European Scientific Journal, ESJ, 2022)
The purpose of this article is to present a review of the literature on the variables that can influence students' entrepreneurial intention, as well as the theories underlying our research work. Several theories have been mobilized to explain entrepreneurial intention, notably Sokol and Shapero's theory (1982) and Ajzen's theory (1991). But among students in particular, we must ask what factors spark the idea of starting a business.  After examining several articles in the literature on entrepreneurial intention (about thirty), we were able to identify, through an archiving method, three essential variables that act on entrepreneurial intention: The desire to undertake, the social factor and the degree of feasibility. But isn't it important to look at other variables that can influence the entrepreneurial act ?